Розробка програмного забезпечення для розміщення вакансій - Кузнєцов, Д. О. (ХНУРЕ, 2024)
This work was created with the aim of developing an up-to-date workable model related to the placement of a finished product that will be competitive in the labor market and will be relevant for a wide range of clients. The application is a web development for distributing content related to resumes, vacancies, and projects. It is completely competitive and implements all the necessary functionality. The program is capable of storing, searching and retrieving the necessary data for the client, such as information about the client, projects, vacancies, all relevant data, and is also capable of validating them.
Keywords: розміщення вакансій; вакансія